Technical low-frequency magnetic noise in Kiev - Orlyuk, M. I.; Romenets, А.A.; Orliuk, I.M. (Reports of the National Academy of Sciences of Ukraine, 2014)
The technical nature of magnetic field variations researched in Kiev is presented. The man-made component of the magnetic field in the frequency range from 10−6 Hz to 1 Hz is experimentally studied for the first time. It is shown that technological variation sources which have intensity of tens and hundreds of nanoteslas mostly have electrical and ferromagnetic nature. People and manufacture timetables cause the circadian rhythm of technological variations.